Low cost real time braille keypad for communication - Prabha.P, Lakshmi; EJ, Sanjanamenon; Samuel, Christina; Ramesh, Ganga (International Journal of Engineering and Technology, 2018)
Visually impaired people find it challenging to use devices such as computers, and other digital/educational software like every normal person does in this technology driven world. Due to their inability to gainaccess to basic and vital information they sometimes feel excluded from the society and also limit their knowledge. Several attempts have beenmade in the recent years toimprove their communication methods such as tactile sign language, Braille glove, and Audioacces devices so on. This paper suggests an innovative assistive device, a Braille keypad, for the viually impaired that would help them use computers just like a normal person. The Braille keypad implements the Braille cells as 6 switches that can be pressed simultaneously based on the actual Braille combination in order to type a particular letter and words. The corresponding letters/words are displayed as well as can be heard by the user. A text to speech algorithm is implemented using puTTY software which would help the user confirm what he/she has typed is right. In this way it enables them to interact and communicate as well as use computers and mobile phones much like a normal person.